The Effect Of Competence and Motivation on Teacher Performance In Development Technology Vocational School Bekasi West Java - Farida, Ida; Tippe, Syarifudin; Tunas, Billy (Asia Pacific Journal of Management and Education (APJME), 2020)
Educational problems are very complex problems if not addressed by staying targeted. Where education here will create students who will jump in the wider community to run life as a wider community. The teacher is the most influential component in the creation of quality education processes and results, therefore any improvement efforts made to improve the quality of education will not make a significant contribution without being supported by teachers of high quality teacher competence. Teacher Competence has a positive effect on Teacher's performance, Motivation has a positive effect on teacher performance, and Teacher competency and motivation together influence teacher performance.